Effects of injection timing on bio-diesel fuelled engine characteristics—An overview. (October 2015) - Panneerselvam, N.; Murugesan, A.; Vijayakumar, C.; Kumaravel, A.; Subramaniam, D.; Avinash, A.
Abstract: In day to day life, we are in need of alternative fuel to create an eco-friendly environment and also to meet out the increasing energy consumption rates. The specific characteristics such as renewability, sustainability and clean burning capacity put ahead the bio-diesels as one among the best choice for alternative fuels. Though there are several ideas and technologies to confront the challenges, they are often confined to a distant future, especially with regard to C.I engines. This review depicts how straight vegetable oil affects the fuel injection nozzle, ring sticking, dilution of the lubricating oil. Also, the different techniques of biodiesel production from straight vegetable oil (SVO) are included. The variables affecting the transesterification reaction, advantages, disadvantages of different types of bio-diesel productions and properties are discussed. The distinct factors of performance and emissions decide the use of fuels in engines. A brief discussion is made on the performance, emission and combustion characteristics of various bio-diesel sources like edible oil, inedible oil, and waste plastic oil. This paper goes on to talk of the advance, retardation methods to treat NO x, HC and CO, and finally a comparative evaluation has been made on coated and uncoated engines with thermal barrier. The energy study for cost of plantation of nonedible oil seeds and cost of bio-diesel production are also discussed.